Development of Conceptual Model for Social Media Characteristics and Consumers’ Purchase Intention - Kajanthy, K.; Sathana, V. (Vavuniya Campus of the University of Jaffna, 2018)
Social media marketing is an evolving topic in the marketing field. During the past decade, the fast pace of web-based technology led to a drastic change in the way we do marketing. The rapid evolution of the internet and specifically the social media has offered consumers countless new opportunities to search and share information about products and services from the desk itself with less effort rather going out to field (Khatib,2016). Earlier days, consumers were waiting for companies to push messages toward them but now directly seeking information on social media. In this manner, under the web-based technology, social media as everybody knows and familiars with their use have already become part of daily routine of most people, it would majorly impact on inducing consumers’ purchase intention. As social media is penetrating rapidly into the society, organizations are ever more adapting them as a partner of their promotional and brand enriching activities (Gallaugher&Ransbotham, 2010). Even though Social Media is being recognized as a powerful bondage between consumers and organizations, a small number of organizations feel comfortable in the adaptation of this new phenomenon (Kaplan &Haenlein, 2010; Bartlett, 2010; Hackworth & Kunz, 2011) because the influence of social media on consumers’ purchase intention is still unclear among them. Thus it is essential to emphasize the influence of social media on consumers’ purchase and business success (Smith, 2011). Even though only a small number of organizations feel comfortable in the adaptation of this new phenomenon (Kaplan &Haenlein, 2010; Bartlett, 2010; Hackworth & Kunz, 2010). Recent studies consider social media as a newly emerging promotional tool (Berinato&Clark, 2010) that upsurges marketing communication successfully (Dholakia & Durham, 2010; Kozinets, De Valck, Wojnicki&Wilner, 2010; Trusov, Bucklin & Pauwels, 2009), and very few emphasis on how firms may benefit from them (Dong-Hun, 2010). To the best of our knowledge, there is a lack of studies examining the impact of social media on consumers’ purchase intention. Taprial and Kanwar (2012) stated five properties that are more powerful and distinguish the social media from traditional media. They are accessibility, speed, interactivity, longevity and reach. Pjero and Kercini (2015) had researched by focusing on social media and its influence on consumer behavior, observed that information about products and services offered in the virtual world could positively impact on consumers’ purchase intentions. At present, more good responses on the products or services, the more attractiveness for consumer purchasing come from social media platforms. Most of the top brands and services noticed it and started to focus on social media marketing. Given the growing number of Internet users, the factors of social media that influence the purchase intention of customers need to be explored (Kaplan&Haenlein, 2010). Social networking sites of brands assist in making better decisions than before purchasing goods and services (Wang & Chang, 2013). Considering this gap, the present study mainly focuses on analyzing the past studies to prepare the future research on consumers’ purchase intention with social media. In the current scenario of marketing, in order to do the promotional activities effectively, it is very appropriate to develop propositions and a new model to make firms to get very much understanding of the importance of social media in terms of building consumers’ purchase intention. Because, the higher the purchase intention, the higher a consumer’s readiness to purchase a product (Husnain, Qureshi, Fatima&Akhtar, 2016). The problem statement of this study is “What are the characteristics of Social media influence on consumers’ purchase intention?” The research objective is to diagnose the future propositions for the association between social media and consumers’ purchase intention.